1971
DOI: 10.1002/ijch.197100050
|View full text |Cite
|
Sign up to set email alerts
|

On the Interpretation of Reaction Rates in Concentrated Acid Solutions

Abstract: The model of Bascombe and Bell for the indicator acidity of concentrated acid solutions is applied to the analysis of acid catalyzed reactions. A number of well studied reactions are shown to obey the relationship: where Cw is the molar concentration of water not bound to proton (or to hydroxyl OH−). Values of Cw for use in the above correlation are calculated, assuming the existence of the proton in the form suggested by Eigen, H3O(H2 O)3+. The volume fractions of nonbound water are also calculated, this q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Bascombe and Bell [ 1 ] have suggested that this behavior may be caused by the decrease in water solvent concentration due to hydration of the proton with four molecules of water [2]. The subject has been reviewed recently [3,4]. The same argument can be applied to determine the hydration number of salts.…”
mentioning
confidence: 99%
“…Bascombe and Bell [ 1 ] have suggested that this behavior may be caused by the decrease in water solvent concentration due to hydration of the proton with four molecules of water [2]. The subject has been reviewed recently [3,4]. The same argument can be applied to determine the hydration number of salts.…”
mentioning
confidence: 99%